Analysis and Development of Laboratory Information Systems (case Study : Informatics Engineering Laboratory, Bhayangkara University, Surabaya) - Syariful Alim; M Mahaputra Hidayat; Muchammad Faisal Aditya (Fakultas Teknik Universitas Bhayangkara, 2021)
At first information systems do not have to be associated with information technology, but with the development of the times, nowadays an information system can not exist without the use of information technology. A system is needed to facilitate the affairs of an organization. The effecctiverss of the system will affect the success of the organization under it. The development of Web-based Information Systems is an effort to develop the implementation of practice and in order to improve the quality of services to students that are effective, efficient and transparent, and directed to achieve the establishment of information networks and service transactions to qualified students without restrictions on partition and space. The end goal is the development of Laboratory Information System is expected to accommodate the concept, the essence and the nature of service to students with excellenees. The results of the test based on questionnaire data. Presentase conformity system reach 92%, where the system runs in accordance with the wishes of responden. While the system discrepancies reach 8%.